Intermediate Algebra (6th Edition)

Published by Pearson
ISBN 10: 0321785045
ISBN 13: 978-0-32178-504-6

Chapter 5 - Section 5.3 - Polynomials and Polynomial Functions - Exercise Set: 114



Work Step by Step

We are given that $P(x)=3x+3$ and $Q(x)=4x^{2}-6x+3$. $P(x)-Q(x)=(3x+3)-(4x^{2}-6x+3)=(3x+3)+(-4x^{2}+6x-3)$ Combine like terms. $-4x^{2}+(3x+6x)+(3-3)=-4x^{2}+9x$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.